Edukasi Pentingnya Pengelolaan Waktu untuk Mengurangi Dampak Negatif Smartphone - Ma’ruf; Amal, Amri; Azifa, Nur; djabir, Sudarni (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
The increasing use of smartphones among elementary school students has the potential to have negative impacts if not accompanied by proper time management. This Community Service (PKM) activity aims to educate students about the importance of time management to reduce the negative impacts of smartphone use. The activity was conducted at Tamannyeleng Elementary School in Gowa Regency, involving 38 students using an educational and participatory approach through material delivery, discussions, and Q&A sessions. The results of the activity showed an increase in students' understanding and awareness of the impacts of uncontrolled smartphone use and the importance of dividing their time between studying, playing, resting, and smartphone use. The approach used also increased student engagement during the activity. This activity has the potential to be the first step in developing wiser smartphone habits in elementary school students.